(untitled) (World Marxist Review, 2026)
The World Association for Political Economy (WAPE) is pleased to announce its annual forum on the theme “The Wealth of Nations in the Multipolar Age”, marking the 250th anniversary of the publication of Adam Smith’s Wealth of Nations. We meet at the Old Royal Naval College in Greenwich, London, where the first Chinese translator of Smith’s works and first principal of Beijing University, Yan Fu, studied.